2018
DOI: 10.4103/ijdr.ijdr_106_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of salivary sialic acid levels in patients with chronic obstructive pulmonary disease and chronic periodontitis patients: A biochemical study

Abstract: We can thus conclude that promotion of dental care knowledge is very much essential in the prevention and treatment of COPD. Thus, estimation of levels of salivary sialic acid can be used as an adjunct to diagnose the current periodontal disease status and to assess the treatment outcomes in subjects with COPD and chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The clinical observation and experimental models described an enhanced level of total serum sialic acid and sialoglycans on the human vein endothelial cells as a marker of pathology and significant risk factor of coronary artery disease (CAD) and angiopathy [ 91 , 92 ]. Moreover, the glycome analysis in asthma and COPD showed that the alterations in sialoglycans correspond to the progress of disease [ 93 , 94 , 95 ]. According to Guo, the lung pathology inducing factors, e.g., tobacco, can be considered as the crucial players in the promotion of SARS-CoV-2 infection and associated with the risk of severe COVID-19 [ 95 ].…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…The clinical observation and experimental models described an enhanced level of total serum sialic acid and sialoglycans on the human vein endothelial cells as a marker of pathology and significant risk factor of coronary artery disease (CAD) and angiopathy [ 91 , 92 ]. Moreover, the glycome analysis in asthma and COPD showed that the alterations in sialoglycans correspond to the progress of disease [ 93 , 94 , 95 ]. According to Guo, the lung pathology inducing factors, e.g., tobacco, can be considered as the crucial players in the promotion of SARS-CoV-2 infection and associated with the risk of severe COVID-19 [ 95 ].…”
Section: Sialic Acids In Covs Infectionsmentioning
confidence: 99%
“…Periodontitis is a chronic infectious disease caused by infectious bacteria and host response and associates with many other systematic diseases. [1][2][3] Periodontitis can lead to destruction of tooth supported tissues, which makes it the main cause of tooth loss of adults. 4,5 Conventional treatments including debridement of the tooth root surface, guided tissue regeneration (GTR) and bone graft placement failed to reach satisfactory curative effect.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a chronic infectious disease caused by infectious bacteria and host response and associates with many other systematic diseases 1,2,3. Periodontitis can lead to destruction of tooth supported tissues, which makes it the main cause of tooth loss of adults 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a wide-spread chronic infectious disease that can destruct teeth supporting tissues, associates with many other diseases, and is the main cause of tooth loss of adults [ 1 5 ]. While the effects of restoring hard and soft periodontal tissues by conventional treatments remain unsatisfactory [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%